SiRNA-Induced Mutation in HIV-1 Polypurine Tract Region and Its Influence on Viral Fitness - Rausch, Jason W.; Tian, Meijuan; Li, Yuejin; Angelova, Lora; Bagaya, Bernard S.; Krebs, Kendall C.; Qian, Feng; Zhu, Chuanwu; Arts, Eric J.; Le Grice, Stuart F. J.; Gao, Yong (PLOS ONE, 2015)
Converting single-stranded viral RNA into double stranded DNA for integration is an essential step in HIV-1 replication. Initial polymerization of minus-strand DNA is primed from a host derived tRNA, whereas subsequent plus-strand synthesis requires viral primers derived from the 3′ and central polypurine tracts (3′ and cPPTs). The 5′ and 3′ termini of these conserved RNA sequence elements are precisely cleaved by RT-associated RNase H to generate specific primers that are used to initiate plus-strand DNA synthesis. In this study, siRNA wad used to produce a replicative HIV-1 variant contained G(-1)A and T(-16)A substitutions within/adjacent to the 3′PPT sequence. Introducing either or both mutations into the 3′PPT region or only the G(-1)A substitution in the cPPT region of NL4-3 produced infectious virus with decreased fitness relative to the wild-type virus. In contrast, introducing the T(-16)A or both mutations into the cPPT rendered the virus(es) incapable of replication, most likely due to the F185L integrase mutation produced by this nucleotide substitution. Finally, the effects of G(-1)A and T(-16)A mutations on cleavage of the 3′PPT were examined using an in vitro RNase H cleavage assay. Substrate containing both mutations was mis-cleaved to a greater extent than either wild-type substrate or substrate containing the T(-16)A mutation alone, which is consistent with the observed effects of the equivalent nucleotide substitutions on the replication fitness of NL4-3 virus. In conclusion, siRNA targeting of the HIV-1 3′PPT region can substantially suppress virus replication, and this selective pressure can be used to generate infectious virus containing mutations within or near the HIV-1 PPT. Moreover, in-depth analysis of the resistance mutations demonstrates that although virus containing a G(-1)A mutation within the 3′PPT is capable of replication, this nucleotide substitution shifts the 3′-terminal cleavage site in the 3′PPT by one nucleotide (nt) and significantly reduces viral fitness.